Induction of CD4+ T-cell anergy and apoptosis by activated human B cells - Tretter, Theresa; Venigalla, Ram Kumar Chowdary; Eckstein, Volker; Saffrich, Rainer; Sertel, Serkan; Ho, Anthony Dick; Lorenz, Hanns-Martin (Blood, 2008)
B cells are well-known mediators of humoral immunity and serve as costimulators in the generation of T cell-mediated responses. In several mouse models, however, it was observed that B cells can also down-regulate immune reactions, suggesting a dual role for B cells. Due to this discrepancy and so far limited data, we directly tested the effects of primary human B cells on activated CD4+ T helper cells in vitro. We found that under optimal costimulation large, activated CD25+ B cells but not small CD25− B cells induced temporary T-cell anergy, determined by cell division arrest and down-regulation of cytokine production. In addition, large CD25+ B cells directly induced CD95-independent apoptosis in a subpopulation of activated T cells. Suppression required direct B-T-cell contact and was not transferable from T to T cell, excluding potential involvement of regulatory T cells. Moreover, inhibitory effects involved an IL-2-dependent mechanism, since decreasing concentrations of IL-2 led to a shift from inhibitory toward costimulatory effects triggered by B cells. We conclude that activated CD25+ B cells are able to costimulate or down-regulate T-cell responses, depending on activation status and environmental conditions that might also influence their pathophysiological impact.